Research priority-setting for human, plant, and animal virology: an online experience for the Virology Institute of the Philippines - Reneepearl Kim Sales; Joseph Oraño; Rafael Deo Estanislao; Alfredo Jose Ballesteros; Ma. Ida Faye Gomez (BMC, 2021)
Abstract Background Viral pandemics have had catastrophic consequences on population health and economies. The Philippine government intends to establish the Virology Institute of the Philippines, one of the key areas of which will be virology research. This project aimed to develop the institute's research agenda across the fields of human, plant, and animal virology. Methodology Key considerations for the prioritization methodology were (1) the imminent establishment of the Virology Institute of the Philippines, (2) mobility restrictions caused by the coronavirus disease 2019 (COVID-19) pandemic, (3) the timeline to develop the research agenda, and (4) the need to separate the research agenda for the three fields of human, plant, and animal virology. The process was fully conducted online in four steps: stakeholder identification, soliciting research priorities, generating initial research priorities, and final prioritization consultations conducted on Zoom Pro. Results Twenty-eight participants attended three online consultations between 21 and 27 July 2020 through Zoom Pro. Participants selected the research prioritization criteria and its weights, and used these to evaluate the research priorities. The final research agenda covers topics in epidemiology, diagnostics, surveillance, biosafety, and genomics. Conclusion This initiative resulted in the first research agenda for the Virology Institute of the Philippines across the three fields of human, plant, and animal virology. An expert-driven process which places a premium on consensus-building facilitated through online platforms was the most feasible approach to develop the research agenda. This process resulted in an agenda aligned with the mandates of national research councils but leaves gaps on areas such as emerging infectious diseases. Pre-COVID-19 literature expressed apprehensions on the online medium that weakens social ties necessary for consensus. Our experience with changing the mode of consensus-building shows that users will continually adapt to technology. Online tools are currently able to address the limitations of the virtual space.